Self-efficacy, Quality of Work Life, and Organizational Commitment as Predictors for Work Engagement in Primary Healthcare Centers of Riyadh First Cluster, Saudi Arabia - Nassani, Abdelmohsen; Alkhulaifi, Abdulaziz; Almuhawis, Muhammed; Alnujaidi, Muhammad (The Arab Journal of Administration, 2023)
The purpose of this study was to examine the effects of self-efficacy, quality of work life, and organizational commitment as independent variables on work engagement. The study was conducted on employees of Primary Healthcare Centers of Riyadh first cluster in Saudi Arabia. The data was collected using electronic questionaries and there were 222 respondents. The data was analyzed through descriptive statistics (mean, standard deviations, and correlation). Also, reliability analysis was applied to the data. Regression analysis was used to examine the influence of self-efficacy, quality of work life and organizational commitment on work engagement. The correlation between the quality of work life, organizational commitment, and work engagement was significantly high while it was moderately positive between self-efficacy and work engagement. This study is useful for top management and HR specialists. It demonstrates that in order to get employees engaged, it’s necessary to provide them with high quality of work life, ensure they are committed to the organization and recruit employees with high self-efficacy.